Identifikasi dan Uji Patogenisitas Colletotrichum spp. dari Cabai Merah (Capsicum annuum): Kasus di Kricaan, Magelang, Jawa Tengah - Noorkomala Sari; Rina Sri Kasiamdari (Jurnal Ilmu Pertanian Indonesia, 2021)
The investigation of the agent causing diseases is the first step to determine and control the spread of diseases. Anthracnose causing fruit rot on the red pepper in Indonesia that reduces the yield up to 90%. Colletotrichum is reported as the causative fungal agent of anthracnosis on the red pepper. This study aims to determine the type of Colletotrichum spp. pathogenic fungi on the red pepper collected from Agricultural Field Kricaan, Magelang, Central Java. Methods of identification included macroscopic and microscopic characterization and followed by determining the pathogenicity of the pathogenic agent. In this study, Colletotrichum gloeosporioides and C. acutatum are identified as the causative agents of anthracnose in the red pepper collected from the study location. C. acutatum PC3 strain is identified as the most virulent pathogenic agent. Keywords: anthracnosis, diagnosis, diseases, symptoms, pathogen